(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The Committee on the Rights of Persons with Disabilities established with the United Nations Convention on the Rights of Persons with Disabilities adopted on 13 December 2006 is the main human rights treaty body dealing with the rights of persons with disabilities. The Committee under the Optional Protocol of the abovementioned Convention is mandated inter alia to receive and consider communications from or on behalf of individuals or groups of individuals subject to jurisdiction of concrete State Party to the Optional Protocol who claim to be a victim of a violation by that State Party of the provisions of the Convention. This paper explores the modality of the work of the Committee dealing with admissibility of the communications and the merits, and the legal nature of its suggestions and recommendations submitted to the State Party concerned and to the petitioners. Furthermore, the paper analyses in total the jurisprudence of the Committee on the Rights of Persons with Disabilities till nowadays and its adopted views on variety of articles of the Convention. Finally, the paper presents ways forward in increasing the importance of the adopted views of the Committee in safeguarding the fundamental rights enshrined in the Convention. The text uses the jurisprudence of the Committee as well as reports and analysis that have been developed on the same subject matter.